Analisis Energi Pembangkit Listrik Tenaga Uap (PLTU) Dual Fuel Line 3 PT. Riau Andalan Pulp And Paper Pangkalan Kerinci - Aris Freddy; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Steam Power Plant (PLTU) plays a major role in the supply of electricity in Indonesia today. In general, the performance of the power plant is evaluated by using the first thermodynamic law (energy conservation law). For this reason, energy analysis is based on the first law of thermodynamics which can be studied more deeply about the amount of energy in each component of the power plant. The purpose of this study was to analyze the amount of energy in each component in the dual fuel line 3 steam power plant PT. Riau Andalan Pulp and Paper Pangkalan Kerinci. The results showed that the energy value at pump I was (0.006 MW) followed by pump II (2.219 MW), Steam Turbine (88.719 MW), boiler (258,019 MW) and condenser (76.83 MW). Thermal efficiency of the whole system was 33.52%. Keywords: energy analysis, thermal efficiency, biomass